Peran Kepatuhan Wajib Pajak Penghasilan dalam Menjamin Keberlanjutan Penerimaan Pajak Nasional Negara - Herlinanur, Nanda; Reski Apriyani; Putri Rahmawati; Wahjoe Pangestoeti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study examines in depth the contribution of income taxpayer compliance to the sustainability of national tax revenue in Indonesia in the context of the self-assessment system. Using a descriptive qualitative approach, this study analyzes the determinants of compliance, such as tax understanding, tax authority service quality, perceived system fairness, and the effectiveness of tax socialization. The results show that increasing compliance not only has a direct impact on optimizing state revenue, but also strengthens public trust in the government and supports sustainable economic development. Digital innovations such as e-filing and e-SPT are proven to accelerate the reporting process and expand the tax base, thus becoming a strategic element in building a tax-aware culture. This research emphasizes the importance of an educative approach and inclusive public services to create a fair, efficient, and sustainable tax system.